JUMPA Vol.3 No.1 Feb 2016 HUMAN CAPITAL SEBAGAI ASET PALING UTAMA BAGI PERUSAHAAN: HUMAN CAPITAL SEBAGAI ASET PALING UTAMA BAGI PERUSAHAAN - Setyani Dwi Lestari Universitas Budi Luhur (Jurnal Manajemen dan Perbankan (JUMPA), 2016)
This study aims to explain that human capital is the best company’s asset for sustainable competitive advantage, which is the best employees in a company can contribute well for increasing the performance. Human capital is one of the main component from intellectual capital or intangible asset owned by company. In fact, human capital management in company will be the success key to increase its productivity that will have an impact on increasing the total revenue’s company. Those factors are new opportunities for a company, but it is difficult to measure it.